Tom Stoppard: Plays Two - Stoppard, Tom (Contemporary classics, 2012)
This second collection of work by Tom Stoppard contains his radio plays, written between 1964 and 1991. These plays reflect the full range of Stoppard's gifts as well as his craftsmanship and versatility. His work for radio complements (and sometimes prefigures) his work for the stage.